PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII3 SMP NEGERI 4 SIAK HULU - Wandasari, Windy Eriza; Kartini, Kartini; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research which aims to improve the learning process and the result of learning mathematics by applying Discovery Learning model. The subject of this research were the students in the class VIII3 of SMP Negeri 4 Siak Hulu that consist of 22 boys and 19 girls at the second semester of academic year 2017/2018. Instruments on this reserach constisted of syllabus, lesson plans and worksheets, and instruments of data collection which is observation sheets and the test result sheets. The function of observation sheet is to obtain data from the learning process, while the function of results sheet of the mathematics learning tests is to obtain the results of the study. The descriptive of observation sheets and students’ mathematic tests showed an improvement of learning process prior to the action on the first and second cycles and improve the students’ achievement of learning mathematic. On the knowledge competence, from the basic score with percentage 41,46% experience improvement in Cycle I with percentage 65,85% and 78,05% in Cycle II. On the skills competence, the number of students who reach the minimum criteria of mastery learning from Cycle I with percentage 73,17% improve to 87,81% in cycle II. Based on the results of this research can be concluded that the implementation of the Discovery Learning model can improve the learning achievement of the second semester students of class VIII3 of SMP Negeri 4 Siak Hulu in the second semester academic year 2017/2018.Keywords: Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.